EFFECTIVENESS OF INNOVATIVE TECHNOLOGIES IN MASTERING CHEMISTRY - Sadikova Mashxura Idilloyevna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: in this article, the role of innovative technologies in the passing of chemistry and the effectiveness of classes with the use of innovative technologies were calculated by studying the general mastery indicators of students.